Role and development pathways of green hydrogen energy toward carbon neutrality targets - Wang Han; Jie Yan; Wenlong Shang (Asian Development Bank Institute (ADBI), 2023)
Hydrogen energy plays a pivotal role in the world's energy transformation, especially green hydrogen energy that produces no carbon emissions. In the future renewable-dominated energy system, on the one hand, green hydrogen energy can be used as long-term energy storage to cooperate with renewable energy with the characteristics of randomness and volatility, thereby improving the utilization rate of renewable energy and the reliability of the power grid; on the other hand, green hydrogen energy can help reduce carbon emissions in industries in which it is difficult to achieve deep decarbonization through electrification. To date, over 40 countries and regions have released strategies for developing hydrogen energy, highlighting its importance in promoting new energy policies. This paper provides a comprehensive review of the role and development pathways of hydrogen energy. The current status and development trends of green hydrogen production technologies, as well as the role and applications of green hydrogen energy, are analyzed in depth first. Then, the policies and related documents of hydrogen energy development in several countries and regions, including the European Union, the United States, Japan, the Republic of Korea, the People's Republic of China (PRC), and Australia, are surveyed. This paper provides several principles for promoting green hydrogen for countries aiming to formulate the development pathways of hydrogen energy.
Keywords: O33; 330; green hydrogen energy; production technologies; role and applications; development pathways